ANALISIS PENERAPAN AKAD WADIAH DALAM PRODUK TABUNGAN PADA BANK SYARIAH INDONESIA - Fahmi Makraja; Khadijatul Musanna (LPPM IAI Almuslim Aceh, 2023)
Savings products at BSI use a wadiah yad dhamanah agreement, namely the use of customer savings funds by the bank without sharing profits with the customer, but the customer is given a bonus from time to time by the bank according to the management's interruptions. Wadiah yad amanah almost does not exist in Indonesian sharia banks. In muamalah, both in trading and in Islamic banking, Islamic banking has also regulated that it must not harm other parties, must be transparent and there must be no element of usury. This research uses qualitative research. It is hoped that this research will be able to provide a detailed description of the theory regarding the comprehensive systematic application of wadiah contracts regarding matters relating to bank business activities with sharia principles, especially in raising funds, namely wadiah. The results of this research show that the implementation of the wadiah contract using wadiah yad dhamanah in Indonesian sharia banks seems forced in order to attract as many customers as possible, where the majority of the Indonesian population is Muslim, as well as in order to gain the trust of its customers.